2022
DOI: 10.1177/23779608221097450
|View full text |Cite
|
Sign up to set email alerts
|

Between Heaven and Hell: Experiences of Preoperative Pain and Pain Management among Older Patients with Hip Fracture

Abstract: Introduction Among older adults, hip fracture is a common and serious consequence of a fall. Preoperative pain is common and often severe among patients with hip fracture. Opioids are usually used but have many side effects. One alternative is a femoral nerve block, which has been shown to reduce pain and lower the need for opioids. However, to our knowledge no study has explored qualitatively how patients with hip fracture experience treatment with femoral nerve block. Objective The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…During the preoperative phase, preparations such as a surgery shower must be made before surgery. A study from Unneby et al (2022) showed that some patients experienced the surgery shower to be the worst part, while a randomized controlled study did not find any significant differences in preoperative delirium when comparing FNB and opioids ( Unneby et al, 2020 ). However, in the present study, participants highlighted how patients suffered less delirium when receiving an FNB instead of opioids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the preoperative phase, preparations such as a surgery shower must be made before surgery. A study from Unneby et al (2022) showed that some patients experienced the surgery shower to be the worst part, while a randomized controlled study did not find any significant differences in preoperative delirium when comparing FNB and opioids ( Unneby et al, 2020 ). However, in the present study, participants highlighted how patients suffered less delirium when receiving an FNB instead of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly nurses with more extended experience seem to prefer alternative pain management ( Shoqirat et al, 2019 ). A study from Unneby et al (2022) showed that patients suggested limiting opioids and that FNB is an excellent alternative if opioids cause side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of the studies on pain management in these patients are focused on the post-operative pain, as if patients’ preoperative pain is not recognized as serious pain. While in a recent study conducted by Unneby et al even though all of the patients received femoral nerve blockades and proper intravenous analgesics, the preoperative pain perceived by patients was describes as “Hovering between heaven and hell” meaning that their pain intensity ranged from having no pain to the worst pain they had ever experienced [ 37 ]. They also reported that some patients did not remember their pain or the pain management they had received due to their memory loss; therefore, having no verbal complaint regarding pain does not necessarily imply the absence of pain in geriatric patients and proper pain management options with least possible adverse events must be introduced for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pain medication was mentioned as a reason for well-managed pain, but some patients claimed that pain relief did not reduce pain and that opioids caused nightmares, hallucinations, and worry about death, prompting them to refuse pain relief. [12] The downsides of intravenous administration include high dosage, limited analgesic efficacy, and the possibility of severe postoperative nausea and vomiting. [13] This paper prospectively analyzes the effects of different analgesic methods on pulmonary function after the hip fracture in the elderly.…”
Section: Introductionmentioning
confidence: 99%